ANALISIS TINGKAT PENYALURAN KREDIT INVESTASI PADA BANK UMUM DI PROVINSI BALI (2010-2019) - Prasetyo, Levina; Zuhroh, Idah (Journal of Financial Economics & Investment, 2022)
The purpose of this study is to determine whether there is an influence on the level of disbursement of investment credit at commercial banks in the province of Bali with the variables used, namely, Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Third Party Funds (DPK) and Inflation in 2010Q1-2019Q4. The data used in this study is secondary data, which comes from the publications of Bank Indonesia in the 2010-2019 Regional Economic Studies. This research uses multiple linear regression analysis method. The results of this study indicate that the NPL variable has a significant negative effect on the level of investment credit distribution, the LDR variable has a positive and insignificant effect on the level of investment credit distribution, the DPK variable has a significant positive effect on the level of investment credit distribution, the inflation variable has a positive and insignificant effect on the level of lending investation. And simultaneously the variables of Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Third Party Funds (DPK), Inflation simultaneously (simultaneously) have a significant effect on the variable of investment credit distribution.